Solid electrolyte layer and all-solid-state battery using the same

By introducing an appropriate amount of carbon particles into the solid electrolytic layer of an all-solid state battery, the mechanical strength of the electrolytic layer and the improvement of the cyclic performance are achieved, the crack problem caused by internal stress of the battery is solved, and the overall performance of the battery is improved.

JP7648534B2Active Publication Date: 2025-03-18TDK CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021556116
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-12
Filing Date
2020-11-11
Publication Date
2025-03-18
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the stress caused by the expansion and contraction of the positive and negative electrode layers in all solid state batteries, resulting in cracks inside the battery, increasing resistance and reducing battery capacity.

Method used

An appropriate amount of carbon is introduced into the solid electrolytic layer of an all-solid state battery, and the mechanical strength of the electrolytic layer is increased through uniform dispersion of carbon particles, reducing stress concentration, and thus suppressing the occurrence of cracks.

Benefits of technology

By introducing carbon particles, the mechanical strength of the solid electrolytic layer and the cycling performance of the battery are significantly improved, the occurrence of internal cracks is reduced, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648534000008
    Figure 0007648534000008
  • Figure 0007648534000009
    Figure 0007648534000009
  • Figure 0007648534000010
    Figure 0007648534000010
Patent Text Reader

Abstract

This solid electrolyte layer has a solid electrolyte and a carbon, and in the solid electrolyte layer, the degree of dispersion of the carbon using the division method (CV value) in a cross section of the solid electrolyte layer is greater than 0 and less than 1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte layer and an all-solid-state battery using the same. This application claims priority based on Japanese Patent Application No. 2019-204386, filed on November 12, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, electronics technology has developed remarkably, and portable electronic devices are being made smaller, lighter, thinner, and more multifunctional. Accordingly, there is a strong demand for batteries that serve as the power source for electronic devices to be smaller, lighter, thinner, and more reliable. Currently, lithium ion secondary batteries that are widely used have traditionally used electrolytes (electrolytic solutions) such as organic solvents as a medium for transferring ions. However, lithium ion secondary batteries with conventional configurations use electrolyte solutions that contain flammable substances such as organic solvents, and care must be taken to prevent the electrolyte from leaking. Therefore, there is a demand for safer lithium ion secondary batteries.

[0003] Therefore, as one measure to improve the safety of lithium-ion secondary batteries, it has been proposed to use a solid electrolyte instead of an electrolytic solution as the electrolyte. Furthermore, development of an all-solid-state battery, which uses a solid electrolyte as the electrolyte and also has other components all made of solids, is underway.

[0004] However, when all the components of a lithium-ion secondary battery are integrated in a solid state, if the positive electrode layer, electrolyte layer, and negative electrode layer expand / contract at different rates during charging / discharging, tensile / compressive stress is applied to adjacent layers, which makes them prone to cracking. Internal cracks increase resistance and increase the dead area that cannot contribute to charging / discharging, leading to a decrease in battery capacity.

[0005] Patent Document 1 describes an all-solid-state lithium battery equipped with an oriented positive plate having a thickness of 30 μm or more and made of an oriented sintered body. In Patent Document 1, in order to prevent electrical short circuits and increased resistance due to cracks, the oriented sintered body contains multiple primary particles made of a lithium composite oxide having a layered rock salt structure, and the multiple primary particles are oriented at an average orientation angle of more than 0° and not more than 30° with respect to the plate surface of the oriented positive plate.

[0006] Patent Document 2 describes an all-solid-state lithium ion battery having a solid electrolyte membrane, the standard deviation of the thickness of which is 5.0 μm or less and which contains an inorganic solid electrolyte material having lithium ion conductivity as a main component. Patent Document 2 describes that the uniformity of the thickness of the solid electrolyte membrane is controlled in order to suppress cracks and produce an all-solid-state lithium ion battery with excellent battery characteristics.

[0007] Patent Document 3 describes a method of baking an unfired body of a solid electrolyte layer containing a de-resin accelerator in order to promote the removal of resin from an all-solid-state battery. A typical method of manufacturing an all-solid-state battery is to disperse an active material and a solid electrolyte in a solution containing a binder and a plasticizer, respectively, to prepare a slurry, and to laminate the active material green sheet and the solid electrolyte green sheet obtained by molding the slurry, and to remove the binder and the plasticizer by pyrolysis, and then to bake the laminate to obtain an all-solid-state battery. Patent Document 3 states that in the laminate of an all-solid-state battery obtained by baking, if the resin such as the binder and the plasticizer is not sufficiently removed, electronic conductivity occurs from carbon or carbide as a residue of the resin, which may cause an internal short circuit between the positive electrode layer and the negative electrode layer via the solid electrolyte layer. In order to prevent this, Patent Document 3 includes a de-resin accelerator in at least the unfired body of the solid electrolyte layer, and then bakes the unfired body.

[0008] As described in Patent Document 3, it has been conventionally considered preferable to have as little carbon or carbide as possible in the solid electrolyte layer constituting an all-solid-state battery in order to prevent an internal short circuit. However, an internal short circuit requires the formation of a conductive path, and the mere presence of residual carbon does not necessarily result in an internal short circuit. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2018 / 025594 [Patent Document 2] JP 2017-157362 A [Patent Document 3] JP 2015-60737 A Summary of the Invention [Problem to be solved by the invention]

[0010] Even if the expansion rate is reduced by orienting the positive electrode as in Patent Document 1, it is not only the positive electrode that expands and contracts during charging and discharging, but also the negative electrode that transfers / releases lithium ions, which is thought to expand and contract significantly. The expansion and contraction of the positive and negative electrodes applies stress to the electrolyte layer sandwiched between the positive and negative electrodes. When the stress is strong, cracks occur and progress in the all-solid-state battery. Since the cracks hinder ion conduction, resistance increases and the battery capacity decreases. Therefore, the cycle characteristics are deteriorated in the invention described in Patent Document 1. In addition, even if the expansion and contraction are made uniform as in Patent Document 2, the positive and negative electrodes expand / contract, and tensile / compressive stress is applied to the adjacent solid electrolyte layer. Therefore, it is speculated that it is difficult to sufficiently suppress the occurrence of internal cracks in all-solid-state batteries with the techniques described in Patent Documents 1 and 2. Therefore, the cycle characteristics are deteriorated even in the invention described in Patent Document 2.

[0011] The present invention has been made to solve the above problems, and an object of the present invention is to provide a solid electrolyte layer having excellent cycle characteristics, and an all-solid-state battery using the same. [Means for solving the problem]

[0012] The solid electrolyte layer of the all-solid-state battery according to the first embodiment of the present invention is a layer having a solid electrolyte and carbon, and the degree of dispersion of the carbon (CV value) measured by a compartment method in a cross section of the solid electrolyte layer is greater than 0 and less than 1.

[0013] Furthermore, the carbon content in the solid electrolyte layer according to the above embodiment may be 0.01 to 1.8% by volume.

[0014] Furthermore, when carbon in the solid electrolyte layer according to the above embodiment is measured by argon laser Raman spectroscopy, -1 The intensity of the G band peak due to the graphite structure present nearby is IG, 1350 cm -1 When the intensity of the D band peak resulting from the disorder of the graphite structure present in the vicinity is defined as ID and the ratio of these is defined as the degree of graphitization (IG / ID), the IG / ID value may be 0.0 or more and 4.0 or less.

[0015] Furthermore, the carbon particles in the solid electrolyte layer according to the above embodiment may have an average particle size of 0.01 μm or more and 1 μm or less.

[0016] Furthermore, the carbon particles in the solid electrolyte layer according to the above embodiment may be diamond or amorphous carbon particles.

[0017] An all-solid-state battery according to a second aspect of the present invention has the solid electrolyte layer according to the above aspect.

[0018] The all-solid-state battery according to the above aspect is an all-solid-state battery including a positive electrode layer, a negative electrode layer, a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and a margin layer arranged adjacent to and on the outer periphery of the positive electrode layer and the negative electrode layer, the margin layer including a solid electrolyte and carbon, and a degree of dispersion (CV value) of the carbon in a cross section of the margin layer according to a compartment method may be greater than 0 and less than 1. Effect of the Invention

[0019] According to the present invention, it is possible to provide a solid electrolyte layer having excellent cycle characteristics, and an all-solid-state battery using the same. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a cross-sectional image showing a configuration of an all-solid-state battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an image diagram of a solid electrolyte and carbon in a solid electrolyte layer according to one embodiment of the present invention. [Diagram 3] 2 is a SEM image (reflected electron image) of a solid electrolyte layer according to one embodiment of the present invention. [Figure 4] 2 is a binarized image of an SEM image (reflected electron image) of a solid electrolyte layer according to one embodiment of the present invention. [Diagram 5] FIG. 2 is a diagram showing a part of a binarized image of a solid electrolyte layer according to one embodiment of the present invention, which is divided into nine squares. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The solid electrolyte layer of the present invention and the all-solid-state battery using the same will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts enlarged for the sake of convenience in order to make the features of the present invention easier to understand. Therefore, the dimensional ratios of each component shown in the drawings may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and can be appropriately modified and implemented within the scope of the present invention.

[0022] First, the directions are defined. The direction in which the positive electrode layer 3 and the negative electrode layer 4, which will be described later, are stacked is defined as the z direction. One of the in-plane directions in which the positive electrode layer 3 and the negative electrode layer 4, which will be described later, extend is defined as the x direction, and the direction perpendicular to the x direction is defined as the y direction.

[0023] (All-solid-state battery) First, the all-solid-state battery according to the present embodiment will be described.

[0024] As shown in FIG. 1, the all-solid-state battery 1 has a laminate 20 and outer layers (cover layers) 6 located on both sides of the laminate 20 in the lamination direction. The laminate 20 has a positive electrode layer 3 and a negative electrode layer 4 alternately laminated with a solid electrolyte layer 2 interposed therebetween. The positive electrode layer 3 is an example of a first electrode layer, and the negative electrode layer 4 is an example of a second electrode layer. One of the first electrode layer and the second electrode layer functions as a positive electrode, and the other functions as a negative electrode. The positive electrode layer 3 has a positive electrode active material layer 3a and a positive electrode collector layer 3b. The negative electrode layer 4 has a negative electrode active material layer 4a and a negative electrode collector layer 4b. A margin layer 5 is formed on the same plane of each of the positive electrode layer 3 and the negative electrode layer 4. The laminate 20 is a hexahedron, and has two end faces (first end face 21, second end face 22) and two side faces (first side face, second side face) formed as faces parallel to the lamination direction, and an upper face 25 and a lower face 26 formed as faces perpendicular to the lamination direction. The positive electrode current collector layer 31 is exposed at the first end face 21, and the negative electrode current collector layer 42 is exposed at the second end face 22. The first side face is the side face on the right side as viewed from the first end face 21 side with the upper face 25 facing up, and the second side face is the side face on the left side as viewed from the first end face 21 side with the upper face 25 facing up. The first end face 21 and the second end face 22 face each other, and the first side face and the second side face face each other.

[0025] A positive electrode external electrode 7 electrically connected to the positive electrode collector layer 3b is provided so as to cover the first end face 21 side of the laminate 20. This electrical connection is achieved by connecting the positive electrode external electrode 7 to the positive electrode collector layer 31 of the positive electrode 30 exposed at the first end face 21 of the laminate 20.

[0026] A negative electrode external electrode 8 electrically connected to the negative electrode collector layer 4b is provided so as to cover the second end face 22 side of the laminate 20. This electrical connection is achieved by connecting the negative electrode external electrode 70 to the negative electrode collector layer 41 of the negative electrode 40 exposed at the second end face 22 of the laminate 20.

[0027] In the following explanation in the specification, either or both of the positive electrode active material and the negative electrode active material may be collectively referred to as the active material, either or both of the positive electrode active material layer 3a and the negative electrode active material layer 4a may be collectively referred to as the active material layer, either or both of the positive electrode current collector layer 3b and the negative electrode current collector layer 4b may be collectively referred to as the current collector layer, either or both of the positive electrode layer 3 and the negative electrode layer 4 may be collectively referred to as the electrode layer, the first end face 21 and the second end face 22 may be collectively referred to as the end face, the first side face and the second side face may be collectively referred to as the side face, and the positive electrode external electrode 7 and the negative electrode external electrode 8 may be collectively referred to as the external electrode.

[0028] The margin layer 5 of the all-solid-state battery 1 of this embodiment is preferably provided when the step is large in order to eliminate the step between the solid electrolyte layer 2 and the positive electrode layer 3 and the step between the solid electrolyte layer 2 and the negative electrode layer 4. The margin layer 5 is preferably provided on the same plane as the positive electrode layer 3 and the negative electrode layer 4. The margin layer 5 may be the same as or different from the solid electrolyte contained in the solid electrolyte layer 2 described later. The presence of the margin layer 5 eliminates the step between the solid electrolyte layer 2 and the positive electrode layer 3 and the negative electrode layer 4, so that the density of the solid electrolyte layer 2 and the electrode layer is increased, and delamination or warping due to firing of the all-solid-state battery is less likely to occur. On the main surface of the solid electrolyte layer 2, the margin layer 5 is formed in an area other than the positive electrode layer 3 and the negative electrode layer 4 at a height approximately equal to that of the positive electrode layer 3 or the negative electrode layer 4 (i.e., arranged side by side on the periphery of each of the positive electrode layer 3 and the negative electrode layer 4).

[0029] (solid electrolyte layer) The solid electrolyte layer 2 according to this embodiment includes a solid electrolyte and carbon, and the degree of dispersion (CV value) of the carbon in a cross section of the solid electrolyte layer is greater than 0 and less than 1, as determined by a compartment method.

[0030] According to this configuration, the solid electrolyte layer 2 has excellent strength as a whole layer due to particle dispersion strengthening described later. Therefore, even if stress due to volume expansion and contraction of the positive electrode active material and the negative electrode active material accompanying charge and discharge reactions is applied, cracks are unlikely to occur in the solid electrolyte layer. As a result, excellent cycle characteristics are obtained.

[0031] In addition to its excellent mechanical strength, carbon is an abundant and relatively inexpensive element, and carbon itself is virtually harmless, making it an excellent additive for the solid electrolyte layer.

[0032] On the other hand, because carbon generally has high electrical conductivity, the continuous presence of carbon makes it more likely for internal short circuits to occur. However, in the solid electrolyte layer 2, the degree of dispersion of carbon measured by the partition method is less than 1, and the connections between the carbon atoms are few, so they do not form conductive paths, and internal short circuits are suppressed.

[0033] 2, the solid electrolyte layer 2 of the present embodiment has a plurality of solid electrolyte particles 11 and carbon particles 12 dispersed among the plurality of solid electrolyte particles 11. Note that FIG. 2 is a schematic diagram showing an example of the internal structure of the solid electrolyte layer 2.

[0034] In the solid electrolyte layer 2, the carbon particles 12 are contained between the solid electrolyte particles 11, and the mechanical strength, such as the fracture toughness, of the entire solid electrolyte layer 2 is improved by particle dispersion strengthening. This is because the carbon particles 12 have excellent mechanical strength. As a result, even if stress due to the volume expansion and contraction of the positive electrode active material and the negative electrode active material accompanying the discharge reaction is applied, cracks are unlikely to occur in the solid electrolyte layer 2. As a result, excellent cycle characteristics are obtained in the all-solid-state battery 1 using this.

[0035] The carbon particles 12 have different effects on improving the mechanical strength of the solid electrolyte layer 2 depending on the degree of graphitization. The higher the strength of the carbon particles 12 itself, the greater the effect of pinning the progression of cracks. When diamond or amorphous carbon particles are used as the carbon particles 12, the strength of the particles themselves is high, and this improves the strength of the entire solid electrolyte layer 2. Therefore, the all-solid-state battery 1 can obtain excellent cycle characteristics.

[0036] The average particle size of the carbon particles 12 is preferably 0.01 to 1 μm. Carbon powder less than 0.01 μm is difficult to disperse and is prone to agglomeration, and carbon particles 12 exceeding 1 μm are too large compared to the solid electrolyte powder. However, by setting the average particle size of the carbon particles 12 to 0.01 to 1 μm, the carbon particles 12 can be easily dispersed uniformly, improving the mechanical strength of the solid electrolyte layer 2 and, as a result, improving the cycle characteristics.

[0037] In the solid electrolyte layer 2 of the present embodiment, the CV value of the degree of dispersion of the carbon particles 12 having a particle size of 0.01 to 1 μm, as determined by a partition method, is preferably less than 1.0.

[0038] In this embodiment, the CV value is used as an index of the even distribution of the carbon particles 12. That is, the lower the CV value, the more evenly the carbon particles 12 are present, and therefore the greater the effect of improving the strength of the solid electrolyte layer 2 as a whole, and the better the cycle characteristics. Furthermore, when the CV value is low, the probability that the carbon particles 12 are continuously present is low, and short circuit defects can be suppressed.

[0039] On the other hand, when the CV value is high, that is, when the carbon particles 12 are unevenly distributed, the probability that the carbon particles 12 are continuously present is high, and the possibility of a short circuit occurring increases. On the other hand, there are also many regions where the carbon particles 12 are not present, and the strength of the entire solid electrolyte layer cannot be improved significantly.

[0040] An example of a backscattered electron image of the solid electrolyte layer 2 taken by a scanning electron microscope (SEM) is shown in Fig. 3. Fig. 4 shows an image obtained by binarizing the image of Fig. 3 using image analysis software. Fig. 5 shows an image obtained by cutting the image shown in Fig. 4 into a square and further dividing the cut square into nine equal squares.

[0041] In this embodiment, a cross section including the interfaces between the solid electrolyte layer 2 and the positive electrode active material layer 3a and the negative electrode active material layer 4a is cut out and then polished, and an SEM image of the polished surface is obtained by a scanning electron microscope (SEM) as shown in Fig. 3. In addition to the SEM image, a TEM image may be obtained by a transmission electron microscope (TEM). Note that, for convenience of explanation, Fig. 3 shows an enlarged view of a portion having a particularly large amount of carbon, but the solid electrolyte layer 2 according to this embodiment is not limited to this example.

[0042] In the SEM image shown in FIG. 3, the phase (main phase) of the solid electrolyte particles 11 is identified as "light colored," and the phase (secondary phase) of the carbon particles 12 is identified as "dark colored."

[0043] In this embodiment, the dispersity of the carbon particles 12 having a particle size of 0.01 to 1 μm is determined by a compartment method using image analysis software.

[0044] Specifically, first, the SEM image is binarized by image processing. For the binarization of the SEM image, a concentration histogram is created from the SEM image by the mode method. In the concentration histogram, the concentration value of the valley at the boundary between the main phase and the subphase is set as the threshold, and the region that is the main phase on either side of the threshold is set as the "bright area," and the region that is the subphase on either side of the threshold is set as the "dark area," and the images are binarized.

[0045] In many cases, a bimodal histogram is obtained, with two peaks on either side of a valley, but there may be cases where two or more valleys are generated. In this case, the valley at the boundary between the main phase and the subphase is selected, and the concentration value of the valley is set as the threshold value.

[0046] Next, the image obtained by binarizing the SEM image is shown in Fig. 4. After the image shown in Fig. 4 is divided into a plurality of equal regions, the number of carbon particles 12 having a particle size of 0.01 µm or more present in each region is counted.

[0047] In this embodiment, the image is divided into nine square regions as shown in Fig. 5. Hereinafter, the nine square regions are referred to as regions R1 to R9, respectively. The number of carbon particles 12 having a particle size of 0.01 µm or more present in regions R1 to R9 shown in Fig. 5 was counted. The results are shown in Table 1 below.

[0048] [Table 1]

[0049] Next, the average value and standard deviation value of the number of carbon particles 12 counted in the regions R1 to R9 were obtained, and the CV value (=standard deviation value÷average value) was calculated. As a result, as shown in Table 1, the average value was 11.1, the standard deviation value was 4.5, and the CV value (=standard deviation value÷average value) was 0.4.

[0050] In the solid electrolyte layer 2 of the present embodiment, the above-mentioned CV value is 1.0 or less, and thus the strength of the solid electrolyte layer 2 is improved by particle dispersion reinforcement. This makes it possible to prevent the solid electrolyte layer 2 from being destroyed by expansion and contraction stress during charging and discharging, and to improve the cycle characteristics of the all-solid-state battery 1.

[0051] On the other hand, when the above-mentioned CV value is 1.0 or more as shown in Table 2 below, for example, when the distribution is as shown in Table 2 below, the carbon particles 12 dispersed among the solid electrolyte particles 11 segregate, and the effect of improving the strength of the entire solid electrolyte layer 2 becomes insufficient. In this case, it is difficult to prevent destruction near the interface between the solid electrolyte layer 2 and the positive electrode active material layer 3a and the negative electrode active material layer 4a during charging and discharging. That is, when the above-mentioned CV value is 1.0 or more, the cycle characteristics of the all-solid-state battery cannot be improved. In addition, the segregated carbon particles 12 tend to form a conductive path. In this case, a short circuit occurs from the first time. It is preferable that the solid electrolyte layer 2 of this embodiment does not contain carbon particles having a particle size of 1 μm or more.

[0052] [Table 2]

[0053] Furthermore, the carbon content in the solid electrolyte layer 2 is preferably 0.01 to 1.8 volume %. The carbon content (volume %) is determined, for example, by volume conversion using the specific gravity of carbon. Specifically, the volume conversion of the carbon amount (volume %) based on the specific gravity is expressed as follows: {(amount of carbon in the solid electrolyte layer (weight %) / specific gravity of carbon (g / cm 3 )} / [{(amount of carbon in the solid electrolyte layer (wt%) / specific gravity of carbon (g / cm 3 )}+{(amount of solid electrolyte in the solid electrolyte layer (wt%) / specific gravity of the solid electrolyte (g / cm 3 The amount of carbon (wt%) in the solid electrolyte layer 2 can be measured, for example, by a method using an electron probe microanalyzer (EPMA (WDS = wavelength dispersive spectroscopy)) or by a method using a carbon-sulfur analyzer (CS-844 (equipment with a similar principle) manufactured by LECO Japan LLC) after separating and collecting a portion of the solid electrolyte layer.

[0054] In addition, when analyzing the carbon amount of the solid electrolyte layer in an all-solid-state battery using a carbon / sulfur analyzer, it requires a large number of all-solid-state battery samples and a lot of labor to separate and collect only the solid electrolyte layer from the laminated and fired product of the all-solid-state battery. Therefore, it is possible to prepare a model sample in which only the solid electrolyte is laminated and co-fire it, and use it for the analysis of the carbon amount instead.

[0055] When the content of the carbon particles 12 is 0.01% by volume or more, a high effect of improving strength can be obtained. Also, when the content of the carbon particles 12 is 1.8% by volume or less, sintering can be facilitated and high initial characteristics can be obtained.

[0056] Moreover, the content of the carbon particles 12 in the solid electrolyte layer 2 is more preferably 0.02 to 0.8% by volume.

[0057] Furthermore, when the carbon particles 12 in the solid electrolyte layer 2 were measured by argon laser Raman spectroscopy, -1 The intensity of the G band peak due to the graphite structure present nearby is IG, 1350 cm -1When the intensity of the D-band peak resulting from the disorder of the graphite structure present in the vicinity is taken as ID and the ratio of these is taken as the degree of graphitization (IG / ID), the IG / ID value is preferably 0.0 to 4.0. Here, in this embodiment, the preferred range of the IG / ID value also includes 0.0.

[0058] The Raman spectrum of carbon materials is generally characterized at 1580 cm -1 The G-band peak appears near 1350 cm -1 It has two characteristic peaks, the G band peak, which appears nearby, and the D band peak, which appears nearby. The G band peak is a peak caused by the vibration of carbon atoms in a hexagonal lattice in the graphite structure, and the D band peak is a peak caused by carbon atoms with dangling bonds, such as in amorphous carbon. As the crystallinity of the carbon material increases, the intensity of the G band peak increases, and as the crystallinity decreases (becomes non-crystallized), the intensity of the D band peak increases.

[0059] Carbon materials with an IG / ID value of 0.0 are diamond crystals, while carbon materials with an IG / ID value of more than 0.0 and less than 4.0 are amorphous carbons, and the mechanical strength of the carbon itself is high. Therefore, the inclusion of these carbons is highly effective in increasing the strength of the solid electrolyte layer.

[0060] In this embodiment, the Raman spectrum of the carbon particles 12 contained in the solid electrolyte layer 2 is measured as follows.

[0061] First, the all-solid-state battery 1 is embedded in a resin such as an epoxy resin and polished so as to be approximately perpendicular to the lamination direction of the solid electrolyte layer 2 to expose the cross section of the solid electrolyte layer 2. Next, the cross section is observed, and a portion where many carbon particles 12 are present within a diameter of 1 μm is selected, and a Raman spectroscopic analysis is performed using an argon laser with a beam diameter of about 1 μm.

[0062] The Raman spectroscopy can be performed using, for example, NRS-7100 manufactured by JASCO Corp. The G band peak intensity (IG) and the D band peak intensity (ID) of each carbon particle 12 are measured, and the ratio between them is defined as the degree of graphitization (IG / ID).

[0063] The solid electrolyte layer 2 of the present embodiment includes a solid electrolyte. The solid electrolyte may be, for example, lithium titanium aluminum phosphate Li 1+x Al x Ti 2-x (PO4)3(0≦x≦0.6), Lithium germanium phosphate Li 1+x Al x Ge 2-x (PO4)3(0≦x≦0.6), Li 3+x1 S x1 P 1-x1 O4(0.4≦x1≦0.6), Li 3.4 V 0.4 Ge 0.6 O4, Li2OV2O5-SiO2, Li2O-P2O5-B2O3, Li 3x La 2 / 3-x TiO3, Li 14 Zn(GeO4)4, Li7La3Zr2O 12、 LiZr(PO4)3. The solid electrolyte layer 2 preferably contains a phosphate, such as lithium aluminum titanium phosphate or lithium germanium phosphate. The shape of the solid electrolyte particle 11 is not particularly limited. The shape of the solid electrolyte particle 11 is, for example, spherical, ellipsoidal, needle-like, plate-like, scaly, tubular, wire-like, rod-like, or amorphous. The particle size of the solid electrolyte particle 11 is, for example, 0.05 μm or more and 50 μm or less, and may be 0.1 μm or more and 10 μm or less. The particle size of the solid electrolyte particle is determined by a measured value (D50) obtained by particle size distribution measurement. D50 is the diameter of a particle at which the integrated value in the distribution curve obtained by the particle size distribution measurement is 50%. The particle size distribution of the particles is measured, for example, by a particle size distribution measuring device using a laser diffraction / scattering method (microtrack method). Furthermore, some of the elements in the solid electrolyte particles 11 may be substituted or the composition ratio may be changed within a range that allows the solid electrolyte layer 2 of this embodiment to function.

[0064] Furthermore, the solid electrolyte layer 2 of this embodiment may be made of a mixture of multiple types of solid electrolytes.

[0065] (Positive electrode active material and negative electrode active material) As described above, one or both of the positive electrode active material layer 3a and the negative electrode active material layer 4a of the all-solid-state battery of the present embodiment contain, for example, lithium vanadium phosphate, lithium vanadyl pyrophosphate, etc. Examples of lithium vanadium phosphate include LiVOPO4, Li4(VO)(PO4)2, Li9V3(P2O7)3(PO4)2, and Li x V2(PO4)3(2.9≦x≦3.5), etc. Examples of lithium vanadyl pyrophosphate include Li2VOP2O7, and Li2VP2O7, etc. The positive electrode active material layer 3a and the negative electrode active material layer 4a preferably contain one or more of the above-described compositions, and particularly preferably contain Li3V2(PO4)3. Furthermore, the Li3V2(PO4)3 contained in the positive electrode active material layer 3a and the negative electrode active material layer 4a is preferably relatively rich in lithium, and it is more preferable if it is Li x V2(PO4)3(3.0<x≦3.4).

[0066] Also, it is preferable that the materials in the positive electrode active material layer 3a and the negative electrode active material layer 4a are exactly the same material. According to such a configuration, a non-polar all-solid-state battery is obtained, so it is also advantageous in that it is not necessary to specify the direction when mounting on a circuit board and the mountability can be significantly improved.

[0067] The positive electrode active material layer 3a and the negative electrode active material layer 4a may contain positive electrode active materials and negative electrode active materials other than lithium vanadium phosphate and lithium vanadyl pyrophosphate. For example, it may contain a conductive assistant, a binder, etc., and preferably contains a transition metal oxide or a transition metal composite oxide. Specifically, the transition metal composite oxide is a lithium manganese composite oxide Li2Mn x3 Ma 1-x3 O3(0.8≦x3≦1, Ma = Co, Ni), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and the general formula: LiNi x4 Co y4 Mn z4A composite metal oxide represented by O2(x4 + y4 + z4 = 1, 0 ≤ x4 ≤ 1, 0 ≤ y4 ≤ 1, 0 ≤ z4 ≤ 1), a lithium vanadium compound (LiV2O5), olivine-type LiMbPO4 (where Mb is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr), Li-excess solid solution cathode Li2MnO3-LiMcO2 (Mc = Mn, Co, Ni), lithium titanate (TiO2, Li4Ti5O 12 )、LiaNi x5 Co y5 Al z5 O2(0.9 < a < 1.3, 0.9 < x5 + y5 + z5 < 1.1), and it is preferably any of these composite metal oxides. Also, the content of these materials is preferably in the range of 1 part by mass to 20 parts by mass with respect to 100 parts by mass of lithium vanadium phosphate in the positive electrode active material layer 3a or the negative electrode active material layer 4a.

[0068] Here, there is no clear distinction between the active materials constituting the positive electrode active material layer 3a or the negative electrode active material layer 4a. By comparing the potentials of the two types of compounds, namely the compounds in the positive electrode active material layer and the compounds in the negative electrode active material layer, the compound showing a nobler potential can be used as the positive electrode active material, and the compound showing a lower potential can be used as the negative electrode active material. Also, if it is a compound that has both lithium ion release and lithium ion occlusion at the same time, the same compound may be used for both the positive electrode active material layer 3a and the negative electrode active material layer 4a.

[0069] (Positive electrode current collector and negative electrode current collector) For the materials constituting the positive electrode current collector layer 3b and the negative electrode current collector layer 4b of the all-solid-state battery of this embodiment, it is preferable to use materials with high conductivity. For example, it is preferable to use silver, palladium, gold, platinum, aluminum, copper, nickel, etc. In particular, copper is less likely to react with the solid electrolyte used in the solid electrolyte layer 2, and is more preferable because it has an effect of reducing the internal resistance of the all-solid-state battery 1. The materials constituting the positive electrode current collector layer 3b and the negative electrode current collector layer 4b may be the same or different.

[0070] Moreover, the positive electrode current collector layer 3b and the negative electrode current collector layer 4b of the all-solid-state battery 1 of this embodiment preferably contain a positive electrode active material and a negative electrode active material, respectively.

[0071] The positive electrode current collector layer 3b and the negative electrode current collector layer 4b each contain a positive electrode active material and a negative electrode active material, thereby improving adhesion between the positive electrode current collector layer 3b and the positive electrode active material layer 3a, and between the negative electrode current collector layer 4b and the negative electrode active material layer 4a.

[0072] The ratio of the positive electrode active material and the negative electrode active material in the positive electrode current collector layer 3b and the negative electrode current collector layer 4b of this embodiment is not particularly limited as long as they function as current collectors. However, it is preferable that the volume ratio of the positive electrode current collector to the positive electrode active material, or the negative electrode current collector to the negative electrode active material, is in the range of 90 / 10 to 70 / 30.

[0073] (Margin layer) The margin layer 5 of the present embodiment is preferably provided in order to eliminate the step between the solid electrolyte layer 2 and the positive electrode layer 3, and the step between the solid electrolyte layer 2 and the negative electrode layer 4. The presence of such a margin layer 5 eliminates the step between the solid electrolyte layer 2 and the positive electrode layer 3, and the step between the solid electrolyte layer 2 and the negative electrode layer 4. This improves adhesion when stacking the all-solid-state battery 1, and further alleviates shrinkage stress during firing, making delamination and warping less likely to occur.

[0074] The material constituting the margin layer 5 may be the same as or different from the solid electrolyte layer 2, and preferably contains the same material as the solid electrolyte layer 2. For example, when the solid electrolyte layer 2 of the present embodiment contains lithium titanium aluminum phosphate as a solid electrolyte, the margin layer 5 also preferably contains lithium titanium aluminum phosphate. In addition, the margin layer 5 may contain multiple types of solid electrolyte materials in accordance with the solid electrolyte layer 2. In this case, it is preferable that the configuration is the same as that of the solid electrolyte layer 2.

[0075] The margin layer 5 of this embodiment preferably has the same solid electrolyte and carbon as the solid electrolyte layer 2 of this embodiment, and further preferably has a carbon dispersion degree (CV value) in the cross section of the margin layer 5 equivalent to that of the solid electrolyte layer 2. That is, it is preferable that the margin layer 5 and the solid electrolyte layer 2 have the same composition and the same carbon dispersion degree (CV value). When the margin layer 5 and the solid electrolyte layer 2 have the same composition and the same dispersion degree, the effect of mitigating shrinkage stress during firing is enhanced, and delamination and warping due to firing are less likely to occur. The carbon dispersion degree (CV value) in the cross section of the margin layer 5 is determined by the same method as the carbon dispersion degree (CV value) in the cross section of the solid electrolyte layer 2.

[0076] (Manufacturing method of all-solid-state batteries) The all-solid-state battery 1 using the solid electrolyte layer 2 of this embodiment can be manufactured by the following procedure: The materials, i.e., solid electrolyte and carbon, positive electrode active material, positive electrode current collector, negative electrode active material, negative electrode current collector, solid electrolyte and carbon for the margin layer, are made into a paste.

[0077] The method for forming a paste of the solid electrolyte and carbon is not particularly limited, but it is preferable to first highly disperse the solid electrolyte powder and carbon among the powders, and then mix the highly dispersed powder with a vehicle to obtain a paste. Here, for highly dispersing the powders, a device that applies compressive, shearing, and impact forces to the powder particles may be used.

[0078] Generally, mixing and dispersion are based on three mechanisms: convection, shear, and diffusion. However, when using nanoparticles such as carbon black as the raw material, it is preferable to mix and disperse them using equipment with mill-like functions (impact, compression, grinding, etc.) that can overcome strong cohesive forces.

[0079] The above-mentioned device is not particularly limited as long as it is a device capable of efficiently dispersing a carbon material such as carbon black and a solid electrolyte, and may be Mechanofusion or Nobilta manufactured by Hosokawa Micron Corp., Theta Composer manufactured by Tokuju Corporation, Hybridizer manufactured by Nara Machinery Works, DMM Mechanochemical Device manufactured by KCK Corporation, or High Speed ​​Planetary Ball Mill manufactured by Kurimoto, Inc. Appropriate conditions are preferably selected depending on the device. For example, Nobilta manufactured by Hosokawa Micron Corp. can efficiently disperse nanoparticle carbon black powder and compound it with the base material solid electrolyte powder by applying three forces of compression, shear, and impact in a well-balanced manner. When the particles are compounded, they can maintain a high dispersion state even in the subsequent process of vehicle mixing.

[0080] Next, the highly dispersed powder is mixed with a vehicle to form a paste. The vehicle is a general term for a medium in a liquid phase, and includes a solvent, a binder, and the like. The binder contained in the paste for forming the green sheet or the print layer is not particularly limited, but polyvinyl butyral resin, polyvinyl acetal resin, cellulose resin, acrylic resin, urethane resin, vinyl acetate resin, and the like can be used, and at least one of these resins is included.

[0081] The paste may contain a plasticizer. The type of plasticizer is not particularly limited, but phthalates such as dibutyl phthalate and benzyl butyl phthalate may be used.

[0082] By this method, a paste for a solid electrolyte layer, a paste for a positive electrode active material layer, a paste for a positive electrode current collector layer, a paste for a negative electrode active material layer, a paste for a negative electrode current collector layer, and a paste for a margin layer are prepared.

[0083] The above-prepared paste for solid electrolyte layer is applied to a substrate such as polyethylene terephthalate (PET) in a desired thickness, and dried as necessary to prepare a green sheet for solid electrolyte layer. The method for preparing the green sheet for solid electrolyte layer is not particularly limited, and known methods such as a doctor blade method, a die coater, a comma coater, and a gravure coater can be adopted. Next, a positive electrode active material layer, a positive electrode current collector layer, and a positive electrode active material layer are printed and laminated in this order on the green sheet for solid electrolyte layer by screen printing to form a positive electrode layer. Furthermore, in order to fill the step between the green sheet for solid electrolyte layer and the positive electrode layer, a margin layer is formed by screen printing in the area other than the positive electrode layer to prepare a positive electrode layer unit.

[0084] Next, a negative electrode active material layer, a negative electrode current collector layer, and a negative electrode active material layer are printed and laminated in this order on the green sheet for the solid electrolyte layer by screen printing to form a negative electrode layer, and a margin layer is formed in an area other than the negative electrode layer by screen printing to fill in any steps, thereby producing a negative electrode layer unit.

[0085] The positive electrode layer units and the negative electrode layer units are alternately laminated by offsetting so that one end of each unit does not coincide with each other, and if necessary, outer layers (cover layers) 6 can be provided on both main surfaces of the laminate. By laminating the outer layers 6, a laminated substrate including a plurality of elements of an all-solid-state battery is produced. The outer layers 6 can be made of the same solid electrolyte and carbon as the solid electrolyte layer 2, and a green sheet for the solid electrolyte layer can be used. When the same green sheet is used, the shrinkage behavior during the firing process is almost the same as that of the solid electrolyte layer 2 of the inner layer, and defects due to differences in shrinkage stress during firing are less likely to occur.

[0086] The manufacturing method according to the present embodiment is for producing a parallel-type all-solid-state battery, but in the manufacturing method of a series-type all-solid-state battery, one end of the positive electrode layer and one end of the negative electrode layer may be stacked so as to coincide with each other, that is, without offsetting.

[0087] Furthermore, the produced laminated substrate can be pressed collectively using a mold press, hot isostatic press (WIP), cold isostatic press (CIP), isostatic press, etc. Pressing is preferably performed while heating, and can be performed at, for example, 40 to 95°C.

[0088] The produced laminated substrate can be cut into laminated bodies of unfired all-solid-state batteries using a dicing device or the like.

[0089] Next, the unfired laminate is debindered and fired. For example, the laminate is heated to 500°C to 750°C in a nitrogen atmosphere to remove the binder. The debindering time is, for example, 1 to 20 hours. After that, the laminate is heated to 600°C to 1000°C in a nitrogen atmosphere to perform firing, thereby obtaining a fired laminate. The firing time is, for example, 0.1 to 3 hours.

[0090] The fired laminate may be placed in a cylindrical container together with an abrasive such as alumina (Al2O3) and barrel polished. This allows the corners of the entire laminate to be chamfered. As another polishing method, sandblasting may be used. This polishing method is preferable because it allows only specific parts of the laminate to be polished.

[0091] Furthermore, in order to efficiently extract current from the laminate after firing, external electrodes 7, 8 can be provided. The external electrodes 7, 8 are connected to one end of the positive electrode layer 3 extending to one side of the laminate 20 and one end of the negative electrode layer 4 extending to one side of the laminate 20, respectively. Thus, a pair of external electrodes 7, 8 are formed so as to sandwich one side of the laminate 20. Examples of methods for forming the external electrodes 7, 8 include a sputtering method, a screen printing method, and a dip coating method. In the screen printing method and the dip coating method, an external electrode paste containing metal powder, resin, and a solvent is prepared, and this is formed as the external electrodes 7, 8. Next, a baking process is performed to remove the solvent, and a plating process for protection and mounting is performed on the surfaces of the external electrodes 7, 8. On the other hand, in the sputtering method, a protective layer and a layer for mounting can be formed on the external electrodes 7, 8, so that the baking process and the plating process are not necessary. Through the steps as described above, the all-solid-state battery 1 can be manufactured.

[0092] The present invention is not necessarily limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention. In other words, the configurations and combinations thereof in the above-described embodiment are merely examples, and additions, omissions, substitutions, and other modifications can be made to the configurations without departing from the spirit of the present invention. EXAMPLES

[0093] Hereinafter, the present invention will be described in more detail based on the above embodiment using examples and comparative examples, but the present invention is not limited to these examples. Note that the "parts" used for the amounts of materials charged in the preparation of the paste mean "parts by mass" unless otherwise specified.

[0094] Example 1 (Preparation of Positive and Negative Electrode Active Materials) The positive and negative active materials used were Li3V2(PO4)3 prepared by the following method. The starting materials were Li2CO3, V2O5, and NH4H2PO4, which were wet mixed in a ball mill for 16 hours. The powder obtained after dehydration and drying was calcined in a nitrogen-hydrogen mixed gas at 850°C for 2 hours. The calcined product was wet ground in a ball mill, and then dehydrated and dried to obtain positive and negative active material powders. The composition of the powder prepared was confirmed to be Li3V2(PO4)3 using ICP emission spectroscopy and X-ray diffraction (XRD).

[0095] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) For both the positive electrode active material layer paste and the negative electrode active material layer paste, 15 parts of ethyl cellulose as a binder and 150 parts of dihydroterpineol as a solvent were added to 100 parts of Li3V2(PO4)3 powder, and the mixture was mixed and dispersed to prepare a positive electrode active material layer paste and a negative electrode active material layer paste.

[0096] (Preparation of paste for solid electrolyte layer) The solid electrolyte was prepared as follows: 1.3 Al 0.3 Ti 1.7 The starting materials were Li2CO3, Al2O3, TiO2, and NH4H2PO4, which were then wet mixed in a ball mill for 16 hours, dehydrated and dried, and the resulting powder was calcined in air at 800°C for 2 hours. After calcination, the powder was wet ground in a ball mill for 16 hours, and then dehydrated and dried to obtain a solid electrolyte powder. The powder produced was Li 1.3 Al 0.3 Ti 1.7 The crystalline phase of (PO4)3 was confirmed using ICP and X-ray diffraction (XRD).

[0097] Next, 100 parts of this solid electrolyte powder was mechanically dispersed with 1000 ppm equivalent (approximately 0.1 part) of carbon black powder. A Nobilta NOB-130 made by Hosokawa Micron Corporation was used as the dispersion device, and the dispersion state was adjusted by the rotor rotation speed and processing time. Although the rotor rotation speed can be up to 6000 rpm, the conditions for the best dispersion state were found by observing with an SEM, and processing was performed at 3000 rpm for 15 minutes.

[0098] Next, 100 parts of ethanol and 50 parts of toluene were added as a solvent to 100 parts of the solid electrolyte powder and 1000 ppm of carbon black powder that had been subjected to the mechanical dispersion treatment, and 16 parts of a polyvinyl butyral binder and 4.8 parts of bis(2-ethylhexyl) phthalate were added. The mixture was wet-mixed in a ball mill for 16 hours as a secondary dispersion to prepare a paste for the solid electrolyte layer.

[0099] Solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The specific gravity of (PO4)3 is 2.93, and that of carbon black is 1.8. When the ratio of carbon to the total powder is calculated by volume conversion, the carbon content is 0.16% by volume. Here, the volume conversion of the carbon amount (volume %) based on the specific gravity is {(amount of carbon in the solid electrolyte layer (weight %) / specific gravity of carbon (g / cm 3 )} / [{(amount of carbon in the solid electrolyte layer (wt%) / specific gravity of carbon (g / cm 3 )}+{(amount of solid electrolyte in the solid electrolyte layer (wt%) / specific gravity of the solid electrolyte (g / cm 3 The carbon content (wt%) in the solid electrolyte layer was determined by a method using EPMA described later. The solid electrolyte content (wt%) in the solid electrolyte layer is calculated by subtracting the carbon content (wt%) in the solid electrolyte layer from 100%.

[0100] (Preparation of sheets for solid electrolyte layer) The paste for the solid electrolyte layer was formed into a sheet using a doctor blade method with a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.

[0101] (Preparation of paste for positive electrode current collector layer and paste for negative electrode current collector layer) To prepare the positive electrode current collector and the negative electrode current collector, Cu and Li3V2(PO4)3 were mixed in a volume ratio of 80 / 20, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added and mixed / dispersed to prepare a paste for the positive electrode current collector layer and a paste for the negative electrode current collector layer.

[0102] (Preparation of margin layer paste) The powder for the margin layer paste is Li, just like the powder for the solid electrolyte layer. 1.3 Al 0.3 Ti 1.7 After subjecting 100 parts of (PO4)3 powder to a mechanical dispersion process for 1000 ppm (approximately 0.1 parts) of carbon black powder, 150 parts of dihydroterpineol as a solvent and 15 parts of ethyl cellulose as a binder were added and mixed / dispersed to prepare a paste for the margin layer.

[0103] (Preparation of external electrode paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting external electrode paste.

[0104] Using these pastes, all-solid-state batteries were fabricated as follows.

[0105] (Fabrication of Positive Electrode Layer Unit) A 5 μm thick positive electrode active material layer (referred to as a first positive electrode active material layer) was formed on the prepared solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick positive electrode current collector layer was formed thereon by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick positive electrode active material layer (referred to as a second positive electrode active material layer) was formed again thereon by screen printing, and dried at 80° C. for 10 minutes to prepare a positive electrode layer on the solid electrolyte layer sheet. Next, a margin layer 9 having a height approximately the same as that of the positive electrode layer was formed on the outer periphery of one end of the positive electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of a positive electrode layer unit.

[0106] (Fabrication of negative electrode layer unit) On the prepared solid electrolyte layer sheet, a 5 μm thick negative electrode active material layer (referred to as the first negative electrode active material layer) was formed by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick negative electrode current collector layer was formed thereon by screen printing, and dried at 80° C. for 10 minutes. Further, a 5 μm thick negative electrode active material layer (referred to as the second negative electrode active material layer) was formed again thereon by screen printing, and dried at 80° C. for 10 minutes to prepare a negative electrode layer on the solid electrolyte layer sheet. Next, a margin layer 9 having a height approximately the same as that of the negative electrode layer was formed on the outer periphery of one end of the negative electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of a negative electrode layer unit.

[0107] (Preparation of Laminate) A laminated substrate was produced by stacking multiple positive electrode layer units and negative electrode layer units alternately while offsetting each other so that one end of each unit did not coincide. In addition, multiple sheets identical to the solid electrolyte layer sheets containing carbon were stacked on both main surfaces of the laminated substrate as outer layers to provide 500 μm outer layers. This laminated substrate was pressed in a hot water isostatic press (WIP) at 80°C and 1 ton, and then cut to produce an unfired laminate.

[0108] (Firing of laminate) The cut laminate was debindered and fired to obtain a fired body. The debindering was performed by increasing the temperature to 500°C at a rate of 50°C / hour in a nitrogen atmosphere and holding the temperature for 2 hours. The firing was then performed by increasing the temperature to 800°C at a rate of 200°C / hour in a nitrogen atmosphere and holding the temperature for 2 hours, and then naturally cooling the laminate and removing it.

[0109] (External electrode formation process) The external electrode paste was applied to the end faces of the fired laminate and heat cured at 150° C. for 30 minutes to form a pair of external electrodes, thus completing a chip-shaped all-solid-state battery.

[0110] In the all-solid-state battery produced in this example, the amount of carbon contained in the solid electrolyte layer can be measured as follows.

[0111] First, the solid-state battery is polished while embedded in a resin such as epoxy resin to expose the cross section of the solid electrolyte layer. At this time, it is preferable to polish it diagonally, close to horizontal, rather than perpendicular to the lamination direction, so that the measurement can be performed over as wide an area as possible. Next, the carbon concentration is measured using EPMA (WDS = wavelength dispersive spectroscopy). The measurement conditions are an acceleration voltage of 10 kV, a measurement current of 500 nA, a peak measurement time of 80 seconds, a background measurement time of 20 seconds, and a minimum spot diameter. It is preferable to use a liquid nitrogen trap for the measurement in order to eliminate the influence of measurement errors caused by hydrocarbon contamination inside the device.

[0112] Similarly, in a state where the all-solid-state battery is embedded in a resin such as an epoxy resin, the solid electrolyte layer is polished so as to be approximately perpendicular to the lamination direction to expose the cross section of the solid electrolyte layer. Then, an SEM image of the exposed cross section of the solid electrolyte layer is obtained, and the degree of dispersion (CV value) is calculated by the image processing and calculation method described above.

[0113] (Examples 2 to 5) The all-solid-state batteries according to Examples 2 to 5 were fabricated in the same manner as in Example 1, except that the conditions for mechanical dispersion in the preparation of the paste for the solid electrolyte layer were changed.

[0114] Comparative Example 1 The all-solid-state battery according to Comparative Example 1 was produced in the same manner as in Example 1, except that no carbon black was added to the paste for the solid electrolyte layer. In order to eliminate the influence of stress due to mechanical dispersion, the solid electrolyte powder alone was treated under the same conditions as in Example 1.

[0115] Comparative Example 2 The all-solid-state battery according to Comparative Example 2 was produced in the same manner as in Example 1, except that the mechanical dispersion condition in the preparation of the paste for the solid electrolyte layer was set to a rotor rotation speed of 6000 rpm. When the powder after mechanical dispersion was observed with an SEM, it was confirmed that when the rotation speed was excessively increased, the solid electrolyte powders were fused together, and the dispersion state with the carbon deteriorated.

[0116] The conditions for mechanical dispersion in Examples 1 to 5 and Comparative Examples 1 and 2 are shown in Table 3.

[0117] [Table 3]

[0118] (Examples 6 to 15) All-solid-state batteries according to Examples 6 to 15 were fabricated in the same manner as in Example 1, except that the amount of carbon black powder added was set to 30 to 15,000 ppm. When the carbon content in the entire powder was calculated in volume terms, the carbon content was 0.00 to 1.8% by volume.

[0119] (Example 16) As in Comparative Example 1, a laminate for an all-solid-state battery was produced without adding carbon black to the paste for the solid electrolyte layer. Then, for the debindering, the temperature was raised to 350°C at a rate of 50°C / hour in a nitrogen atmosphere and held at that temperature for 2 hours. Then, for the firing, the temperature was raised to 800°C at a rate of 200°C / hour in a nitrogen atmosphere and held at that temperature for 2 hours, and then the laminate was taken out after natural cooling. The subsequent steps were the same as in Example 1, and an all-solid-state battery was produced.

[0120] (Examples 17-21) The solid electrolyte is Li 3.6 S 0,6 P 0.4 An all-solid-state battery was fabricated in the same manner as in Example 1, except that the amount of carbon black powder added was changed to 30 to 15,000 ppm. 3.6 S 0,6 P 0.4 The specific gravity of O4 is 2.40 (g / cm 3 ) and when the proportion of carbon in the entire powder is calculated in volume terms, the carbon content is 0.00 to 2.0% by volume.

[0121] Example 22 An all-solid-state battery was fabricated in the same manner as in Example 1, except that the solid electrolyte was changed to LiZr2(PO4)3. The specific gravity of LiZr2(PO4)3 is 3.17 (g / cm 3 ) and when the proportion of carbon in the entire powder is calculated by volume conversion, the carbon content is 0.18% by volume.

[0122] (Example 23) The solid electrolyte is Li 0.34 La 0.51 An all-solid-state battery was fabricated in the same manner as in Example 1, except that TiO3 was used instead. 0.34 La 0.51 The specific gravity of TiO3 is 5.00 (g / cm 3 ) and when the proportion of carbon in the entire powder is calculated by volume conversion, the carbon content is 0.28% by volume.

[0123] (Examples 24-28) The solid electrolyte is Li7La3Zr2O 12 An all-solid-state battery was fabricated in the same manner as in Example 1, except that the amount of carbon black powder added was changed to 30 to 10,000 ppm. 12 The specific gravity of is 5.11 (g / cm 3 ) and when the proportion of carbon in the entire powder is calculated in volume terms, the carbon content is 0.01 to 2.8% by volume.

[0124] (Examples 29 to 34) All-solid-state batteries according to Examples 29 to 34 were fabricated in the same manner as in Example 1, except that the type of carbon added in the preparation of the paste for the solid electrolyte layer was changed. That is, in Examples 29 to 34, carbon black was not added, and other carbons were added. The specific gravity of carbon is 3.52 (g / cm3) for diamond, 3.52 (g / cm4) for diamond, and 3.52 (g / cm5) for diamond. 3 ), and flake graphite is 2.23 (g / cm 3 ), acetylene black and furnace black were the same as in Example 1, 1.8 (g / cm 3 ), amorphous graphite and spheroidal graphite have the same viscosity as flake graphite, 2.2 (g / cm 3 ), the carbon content is 0.08 to 0.16 volume %.

[0125] (Battery evaluation) The all-solid-state batteries produced in the present examples and comparative examples can be evaluated for the following battery characteristics.

[0126] [Calculation of design capacity] The design capacity is determined in advance. To determine the design capacity, the powder of the solid electrolyte is pressed, for example, in a die with a diameter of 12 mm to form a molded body with a thickness of about 1.5 mm, and this molded body is sintered to remove the by-ion to obtain a disk-shaped sintered body. The conditions for the by-ion sintering are the same as those for the chip-shaped all-solid-state battery, such as the atmosphere and temperature, in order to obtain the same battery characteristics as those of the chip-shaped all-solid-state battery. After measuring the thickness of this disk-shaped sintered body, an external electrode paste is applied to both sides of the disk with a diameter of, for example, 7 mm and thermally cured. Then, the charge and discharge characteristics of this disk-shaped solid electrolyte are measured to determine the discharge capacity per unit volume. From this discharge capacity per unit volume, the discharge capacity value when made into a chip shape is calculated and is taken as the "design capacity". Note that, as long as the discharge capacity per unit volume is obtained, the shape of this measurement and the form of the external electrode are not particularly limited.

[0127] [Initial charge / discharge test] The all-solid-state batteries produced in the present embodiment and the comparative example can be evaluated, for example, under the charge and discharge conditions shown below. The charge and discharge current is expressed as C (C) rate hereafter. C rate is expressed as nC (μA) (n is a number) and means a current that can charge and discharge the nominal capacity (μAh) at 1 / n (h). For example, 1C is a charge and discharge current that can charge the nominal capacity in 1 h, and 2C means a charge and discharge current that can charge the nominal capacity in 0.5 h. For example, in the case of an all-solid-state battery with a nominal capacity of 100 μAh, the current at 0.1C is 10 μA (calculation formula: 100 μA × 0.1 = 10 μA). Similarly, the current at 0.2C is 20 μA, and the current at 1C is 100 μA.

[0128] The calculated design capacity was regarded as the nominal capacity, and the battery was charged at a constant current of 0.2 C rate (CC charge) until the battery voltage reached 1.8 V, and then discharged at a constant current of 0.2 C rate (CC discharge) until the battery voltage reached 0 V, and the initial discharge capacity was measured. The percentage of the initial design capacity was calculated using the following formula (1). Initial discharge capacity rate (%) = (initial discharge capacity ÷ design capacity) × 100 (1)

[0129] [Charge / discharge cycle test] The charge-discharge cycle test conditions were constant current charging (CC charging) at a constant current of 0.2 C rate until the battery voltage reached 1.8 V in an environment of 25° C., and then discharging at a constant current of 0.2 C rate until the battery voltage reached 0 V (CC discharging). The above charge and discharge constituted one cycle, and the discharge capacity retention rate after repeating this cycle up to 100 cycles was evaluated as the charge-discharge cycle characteristic. The charge-discharge cycle characteristic in this embodiment was calculated by the following formula. Discharge capacity rate after 100 cycles (%) = (discharge capacity after 100 cycles ÷ initial discharge capacity) × 100 (2)

[0130] (result) Table 4 shows the material specific gravity, carbon amount (ppm by weight), carbon specific gravity, carbon amount (volume %), and carbon dispersion degree of the solid electrolyte layer according to Examples 1 to 5 and Comparative Examples 1 to 2, as well as the initial internal short circuit occurrence rate, the initial discharge capacity rate relative to the design capacity, and the discharge capacity rate after 100 cycles relative to the design capacity of the all-solid-state battery using the same. Here, the carbon amount (ppm by weight) of the solid electrolyte layer is shown in the table as the actual amount measured using an EPMA. 10,000 ppm by weight is 1% by weight. The carbon amount (vol%) of the solid electrolyte layer is shown in the table as the blend weight (ppm) and the volume % calculated from the blend weight and specific gravity. That is, the carbon amount (vol%) of the solid electrolyte layer was calculated by volume conversion based on the specific gravity.

[0131] [Table 4]

[0132] In the all-solid-state batteries according to Examples 1 to 5, the occurrence rate of initial internal short circuit was kept low, while the initial discharge capacity rate was high at 90% or more, and the discharge capacity rate after 100 cycles was also kept at 75% or more, and it was confirmed that they were excellent. This is because the presence of well-dispersed carbon exerts the effect of suppressing internal short circuit while increasing the strength of the solid electrolyte layer.

[0133] In Comparative Example 1, which does not contain carbon, no initial internal short circuit occurred, but the discharge capacity rate was significantly reduced in the initial and after 100 cycles. When the all-solid-state battery of Comparative Example 1 was embedded in epoxy resin after 100 cycles and polished, and the cross section of the solid electrolyte layer was observed, cracks were observed. This is because the battery could not withstand the expansion and contraction stress associated with charging and discharging and thus cracks were generated, resulting in a decrease in capacity.

[0134] On the other hand, in Comparative Example 2, which had the same amount of carbon but poor dispersion, the occurrence rate of the initial internal short circuit was high. It is presumed that the carbon present in large amounts locally formed a conductive path. In addition, the discharge capacity rate after 100 cycles tended to decrease. This is because the carbon was unevenly present, and the effect of increasing the strength of the solid electrolyte layer was not fully exerted in the areas with less carbon.

[0135] Tables 5 and 6 show the specific gravity, carbon amount, and carbon dispersion degree of the solid electrolyte material of the solid electrolyte layer according to Examples 6 to 28, and the internal short circuit occurrence rate after the initial charge / discharge of the all-solid-state battery using the same, the initial discharge capacity rate relative to the design capacity, and the discharge capacity rate after 100 cycles relative to the design capacity.

[0136] [Table 5]

[0137] [Table 6]

[0138] Examples 6 to 15 were produced under the same conditions as Example 1, except for the amount of carbon black powder added. Example 6 had a carbon content of 30 ppm, an equivalent volume of 0.00 volume %, and an initial discharge capacity of 79%. Compared to Example 6, Example 1 had a sufficiently large amount of carbon, and the effect of improving the strength of the solid electrolyte layer was highly obtained.

[0139] On the other hand, in Examples 14, 15, and 21, the carbon amount exceeds 11000 ppm, or 1.8% in terms of volume. However, by improving the carbon dispersion degree compared to Comparative Example 2, the effect of suppressing the occurrence rate of internal short circuits can be obtained. In Examples 1 to 13, 16 to 20, and 22 to 27, the carbon amount is 11000 ppm, or less in terms of volume, or 1.8%, and the occurrence rate of internal short circuits is 10% or less. It is considered that by reducing the amount of carbon, the dispersion degree can be maintained and at the same time, it is difficult to form a conductive path. In addition, by reducing the amount of carbon, the sintering density is easily increased, resulting in an improvement in the initial discharge capacity rate.

[0140] Example 16 is an all-solid-state battery that was produced without adding carbon powder, and by lowering the binder removal temperature, intentionally leaving the binder. The amount of carbon was 1200 ppm by analysis, and since it is assumed to be amorphous carbon, the specific gravity was calculated at 1.8, resulting in a converted volume of 0.20 volume % and a carbon dispersion degree of 0.13, which is close to that of Example 1. Both the initial discharge and after 100 cycles showed good characteristics, and it can be seen that the carbon may be added or may be a residue derived from the binder.

[0141] In Examples 17 to 28, the type of solid electrolyte was changed, and the amount of carbon black powder added was changed in the same manner as in Examples 6 to 15, and the samples were prepared under the same conditions as in Example 1. These Examples also showed higher effects than the Comparative Examples. Since Examples 17 to 21 have solid electrolytes with lower specific gravity than Examples 6 to 15, when the same weight of carbon is added, the volume ratio of carbon shifts relatively to the lower side. With the same weight addition of 12,000 ppm, in Example 14, carbon reaches 1.9 volume % and the initial internal short circuit due to insufficient sintering is >10%, whereas in Example 20, it remains at 1.6 volume %, and the initial internal short circuit is maintained at a low level of <10%. In other words, it can be seen that the effect of carbon is exerted not by weight but by volume ratio.

[0142] In Examples 24 to 28, the type of solid electrolyte was changed, and the amount of carbon black powder added was changed in the same manner as in Examples 6 to 15, and the batteries were manufactured under the same conditions as in Example 1. These Examples also show a higher effect than the Comparative Example. Since Examples 24 to 28 have a higher specific gravity than Examples 6 to 15, when the same weight of carbon is added, the volume ratio of carbon shifts relatively to the higher side. With the same weight addition of 10,000 ppm, in Example 12, the carbon is 1.6 volume %, the initial short circuit is small at <10%, and 80% capacity is maintained after 100 cycles. In Example 28, the carbon reaches 2.8 volume %, leading to insufficient sintering, the initial internal short circuit is >10%, and the capacity after 100 cycles is 71%. These indicators show a higher effect than the Comparative Example. Here again, it can be seen that the effect of carbon is exerted not by weight but by volume ratio.

[0143] From Examples 6 to 28, it is preferable that carbon is present in the solid electrolyte layer in an amount of 0.01 to 1.8% by volume.

[0144] Table 7 shows the results of the carbon IG / ID (degree of graphitization), carbon amount, and carbon dispersion degree of the solid electrolyte layers according to Examples 29 to 34, measured by Raman spectroscopy, as well as the discharge capacity rate after the first charge / discharge relative to the designed capacity of the all-solid-state batteries using the same, and the discharge capacity rate after 100 cycles relative to the designed capacity.

[0145] [Table 7]

[0146] In Examples 29 to 34, all-solid-state batteries were prepared by adding various carbon powders with different manufacturing methods and shapes. Even in Examples 29 to 34, higher effects were obtained compared to the comparative examples. For these Examples, the cross section of the solid electrolyte layer was analyzed by Raman spectroscopy to find the relationship between the graphitization degree (IG / ID value) of carbon and the characteristics. As a result, it was confirmed that diamond or amorphous carbon with a low graphitization degree of 0 to 4.0 had particularly excellent characteristics both at the first discharge and after 100 cycles. Since these carbons have high mechanical strength of the carbon itself, it is considered that the inclusion of them has a high effect of increasing the strength of the solid electrolyte layer. On the other hand, carbon with a graphitization degree exceeding 4, such as in Examples 32 and 33, becomes graphite crystalline, and the effect of increasing the strength of the solid electrolyte layer is lower than in Examples 29 to 31.

[0147] Although the present invention has been described in detail above, the above-mentioned embodiments and examples are merely illustrative. The present invention includes various modifications and alterations of the above-mentioned specific examples within the scope of the gist described in the claims. [Explanation of symbols]

[0148] 1...All-solid-state battery 2...Solid electrolyte layer 3. Positive electrode layer 3a...Cathode active material layer 3b Positive electrode current collector layer 4. Negative electrode layer 4a ··· Negative electrode active material layer 4b ··· Negative electrode current collector layer 5 ··· Margin layer 6 ··· Outer layer 7 ··· Positive electrode external electrode (external electrode) 8 ··· Negative electrode external electrode (external electrode)

Claims

1. A solid electrolyte layer having a solid electrolyte and carbon, a degree of dispersion (CV value) of the carbon by a partition method in a cross section of the solid electrolyte layer is greater than 0 and is not greater than 0.1; the carbon content in the solid electrolyte layer is 0.01 to 0.8% by volume, Solid electrolyte layer.

2. In the argon laser Raman spectrum, -1 The intensity of the G band peak due to the graphite structure present in the vicinity is IG, 1350 cm -1 2. The solid electrolyte layer according to claim 1, wherein the intensity of a D band peak derived from a disorder of a graphite structure present in the vicinity is defined as ID, and the ratio of these is defined as the degree of graphitization (IG / ID). The IG / ID value of the carbon is 0.0 or more and 4.0 or less.

3. 3. The solid electrolyte layer according to claim 1, wherein the carbon particles contained in the solid electrolyte layer have an average particle size of 0.01 μm or more and 1 μm or less.

4. 4. The solid electrolyte layer according to claim 1, wherein the carbon particles contained in the solid electrolyte layer are diamond or amorphous carbon particles.

5. An all-solid-state battery comprising the solid electrolyte layer according to any one of claims 1 to 4.

6. An all-solid-state battery comprising: a positive electrode layer, a negative electrode layer, a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and margin layers arranged adjacent to and around the positive electrode layer and the negative electrode layer, the margin layer includes a solid electrolyte and carbon; The all-solid-state battery according to claim 5 , wherein a degree of dispersion (CV value) of the carbon in a cross section of the margin layer by a partition method is greater than 0 and less than 1.

Citation Information

Patent Citations

  • Manufacture of battery formed entirely of solid lithium

    JP2000311708A

  • Lithium cell

    JP2001126740A

  • Method for producing solid-state battery

    JP2007227362A

  • Method for manufacturing lithium ion secondary battery, and lithium ion secondary battery

    JP2012209218A

  • All-solid type secondary battery

    JP2014192041A